Features of the application of project management in the implementation of agricultural programs - Кantureev, M.T.; Yessengeldina, A.S.; Kosdauletova, R.Ye.; Seitalinova, A.S. (BUKETOV BUSINESS REVIEW, 2017)
This article takes into consideration many features of the state regulation of agriculture with the help of the state programs of the Republic of Kazakhstan. The role of agro-industrial complex in the domestic and foreign markets in connection with the membership of Kazakhstan in the Eurasian Economic Union and the World Trade Organization are also revealed. The authors analyzed the state program for the development of the agro-industrial complex, which is aimed at providing the domestic needs of the population for the demanded types of agricultural products as well as defining targeted export policy. Financial sources for the implementation of the state agricultural program of the Republic of Kazakhstan have been identified and aimed at implementing the priorities of the country's strategic development and ensuring national security. During the research, the authors identified a number of characteristic features of project management, which should be taken into account in the implementation of agricultural programs. The methodological approaches of project management are characterized as following: the approach based on the internal development of projects; an approach based on the high integration of various aspects of project management; an approach based on a model for the development of project management; marketing approach to project management. The article identifies the socio-economic and organizational problems that affect the effectiveness of the agricultural programs implementation by the state. The development of project management in the Republic of Kazakhstan and the possibility of applying the project management mechanism in the implementation of agricultural programs are also considered.